Intercultural contacts in the ancient Mediterranean: proceedings of the international conference at the Netherlands-Flemish Institute in Cairo, 25th to 29th October 2008 - Duistermaat, Kim (Orientalia Lovaniensia analecta, 2011)
The conference Intercultural Contacts in the Ancient Mediterranean (ICAM) was organised in 2008 by the Netherlands-Flemish Institute in Cairo. While Mediterranean contacts in archaeology are a popular topic in Europe, it was the first time this theme was addressed in Egypt. The conference aimed to discuss theoretical and methodological issues related to the study of intercultural contacts in archaeology on the one hand, and to present actual case-studies of such contacts on the other. In the present volume, thirty-five contributions deal with intercultural contacts all over the Mediterranean from the Levant to Spain and from Egypt to Greece, from prehistory up to the Hellenistic period. They are presented in six sections: Theory and methodology, Identifying foreigners and immigrants, Material evidence for contact, Maritime trade and sea ports, Influences in iconography, ideology and religion, and Administration and economy